2015
DOI: 10.1128/aem.02965-14
|View full text |Cite
|
Sign up to set email alerts
|

Entericidin Is Required for a Probiotic Treatment (Enterobacter sp. Strain C6-6) To Protect Trout from Cold-Water Disease Challenge

Abstract: c Flavobacterium psychrophilum causes bacterial cold-water disease in multiple fish species, including salmonids. An autochthonous Enterobacter strain (C6-6) inhibits the in vitro growth of F. psychrophilum, and when ingested as a putative probiotic, it provides protection against injection challenge with F. psychrophilum in rainbow trout. In this study, low-molecular-mass (<3 kDa) fractions from both Enterobacter C6-6 and Escherichia coli K-12 culture supernatants inhibited the growth of F. psychrophilum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Moreover, Millette et al (2008) showed the anti-infective properties of two bacteriocinogenic LAB strains, the NisZ producer L. lactis MM19 and the pediocin PA-1/AcH producer P. acidilactici MM33, which were capable of reducing the intestinal colonization by vancomycin-resistant enterococci in murine models. Recently, Schubiger et al (2015) demonstrated that entericidin produced by the Gram-negative strain Enterobacter sp. C6-6 is required to protect rainbow trout against cold water disease caused by Flavobacterium psychrophilum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Millette et al (2008) showed the anti-infective properties of two bacteriocinogenic LAB strains, the NisZ producer L. lactis MM19 and the pediocin PA-1/AcH producer P. acidilactici MM33, which were capable of reducing the intestinal colonization by vancomycin-resistant enterococci in murine models. Recently, Schubiger et al (2015) demonstrated that entericidin produced by the Gram-negative strain Enterobacter sp. C6-6 is required to protect rainbow trout against cold water disease caused by Flavobacterium psychrophilum.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli ecnAB locus encodes the synthesis of two small lipoproteins that are part the entericidin locus TA system, because of hypothesized similarities to a plasmid addiction module, mazEF , that has been studied in E. coli (24). EcnA was designated as the antitoxin that counteracts the EcnB toxin, whose overproduction results in a more pronounced bacterial lysis than that observed in the co-expression of both ecnA and ecnB (25). Different functions have been proposed for the ecnAB TA system, including programmed cell death (24), adherence in the respiratory tract of humans (26), and its requirement for the probiotic functions of Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Different functions have been proposed for the ecnAB TA system, including programmed cell death (24), adherence in the respiratory tract of humans (26), and its requirement for the probiotic functions of Enterobacter sp. strain C6-6 (25).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these genes have been extensively studied (18,22,23); however, there are genes whose functions in X. citri are still unknown. These genes include the components of the ecnAB toxin/antitoxin (TA) system (XAC_RS20190/ XAC_RS20185 [GenBank database; genome coordinates 4700807 to 4700959/4700598 to 4700732]), which is known to play an important role in Escherichia coli (24,25). The E. coli ecnAB locus encodes two small lipoproteins that are considered to be components of the entericidin locus TA system because of hypothesized similarities to a plasmid addiction module, mazEF, that has been studied in E. coli (24).…”
mentioning
confidence: 99%
“…The E. coli ecnAB locus encodes two small lipoproteins that are considered to be components of the entericidin locus TA system because of hypothesized similarities to a plasmid addiction module, mazEF, that has been studied in E. coli (24). EcnA was identified as the antitoxin that counteracts the EcnB toxin, whose overproduction results in more pronounced bacterial lysis than that observed under coexpression of ecnA and ecnB (25). Different functions have been proposed for the ecnAB TA system, including roles in programmed cell death (24) and adherence to the respiratory tract of humans (26) and a requirement of this system for the probiotic functions of Enterobacter sp.…”
mentioning
confidence: 99%